IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI BERBEASIS PENDEKATAN KONTEKSTUAL DI SEKOLAH DASAR - Siti Rahmah; Ahmad Suriasnyah; Arta Mulya Budi Harsono (STKIP Subang, 2025)
Differentiated learning has become a very important approach in the Kurikulum Merdeka (Independent Curriculum) in meeting the diverse needs, interests, and learning styles of students. Previous research tends to focus on the use of digital media/technology, creating an urgency to describe innovative differentiated implementation strategies using CTL (Contextual Teaching and Learning) / contextual approach in schools with limited facilities, and how this strategy can, of course, influence the teaching and learning process and student learning outcomes in elementary schools. This study uses a qualitative method with a descriptive case study design conducted at SDN Kelayan Timur 7 Banjarmasin, focusing on Grade IV. The participants in this study were one school principal and one teacher, along with 20 students. Data collection was carried out through observation and semi-structured interviews, as well as document analysis. The data was analyzed inductively using an interactive model (data reduction, data display, and conclusion drawing) combined with thematic analysis. The teacher's implementation strategy was carried out through three differentiations: content, process, and product, which were grouped based on the level of ability or learning needs, divided into three categories (Apple, Blueberry, Cherry). The contextual approach was also delivered by integrating the material into everyday life. The impact is that learning becomes more adaptive, relevant, and increases student enthusiasm, as well as showing an improvement between the initial and final assessments. However, the challenges faced also include the demand for extra preparation by the teacher, the need for high levels of attention, and limited learning time. Suggested solutions include utilizing collaboration, peer tutoring, and the teacher's flexible division of attention across all groups. This contextual-based strategy is an effective innovation to be implemented in schools with limited use of digital media/technology facilities.